Associations Between Albuminuria and Mortality Among US Adults by Demographic and Comorbidity Factors - Yelena Drexler; Julien Tremblay; Robert A. Mesa; Bailey Parsons; Efren Chavez; Gabriel Contreras; Alessia Fornoni; Leopoldo Raij; Samuel Swift; Tali Elfassy (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Albuminuria is a known marker of mortality risk. Whether the association between albuminuria and mortality differs by demographic and comorbidity factors remains unclear. Therefore, we sought to determine whether albuminuria is differentially associated with mortality. Methods and Results This study included 49 640 participants from the National Health and Nutrition Examination Survey (1999–2018). All‐cause mortality through 2019 was linked from the National Death Index. Multivariable‐adjusted Poisson regression models were used to determine whether levels of urine albumin‐to‐creatinine ratio (ACR) were associated with mortality. Models were adjusted for demographic, socioeconomic, behavioral, and clinical factors. Mean age in the population was 46 years, with 51.3% female, and 30.3% with an ACR ≥10 mg/g. Over a median follow‐up of 9.5 years, 6813 deaths occurred. Compared with ACR <10, ACR ≥300 was associated with increased risk of mortality by 132% overall (95% CI, 2.01–2.68), 124% among men (95% CI, 1.84–2.73), 158% among women (95% CI, 2.14–3.11), 130% among non‐Hispanic White adults (95% CI: 1.89–2.79), 135% among non‐Hispanic Black adults (95% CI, 1.82–3.04), and 114% among Hispanic adults (95% CI, 1.55–2.94). Compared with ACR <10, ACR ≥300 was associated with increased risk of mortality by 148% among individuals with neither hypertension nor hypercholesterolemia (95% CI, 1.69–3.64), 128% among individuals with hypertension alone (95% CI, 1.86–2.79), and 166% among individuals with both hypertension and hypercholesterolemia (95% CI, 2.18–3.26). Conclusions We found strong associations between albuminuria and mortality risk, even at mildly increased levels of albuminuria. Associations persisted across categories of sex, race or ethnicity, and comorbid conditions, with subtle differences.